KINERJA APARATUR SIPIL NEGARA DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA PROVINSI SULAWESI TEGAH - Putri Handayani; Nawawi Natsir; Nuraisyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to investigate the performance of Civil Servants (ASN) at the Family Planning and Population Control Office of Central Sulawesi Province. Using a qualitative approach, data were collected through in-depth interviews, observation, and documentation. The research findings highlight several performance aspects, including work quality, timeliness, initiative, capability, and communication. Although some employees demonstrate good performance, there are still deficiencies that need to be addressed. In conclusion, the performance of employees at the Family Planning and Population Control Office of Central Sulawesi Province is not optimal, requiring improvements in understanding of job responsibilities, time efficiency, and more effective communication.